Supplemental Foliar-Applied Magnesium Reverted Photosynthetic Inhibition and Improved Biomass Partitioning in Magnesium-Deficient Banana - Hongsu He; Shahbaz Khan; Yan Deng; Haiyan Hu; Liyan Yin; Jiaquan Huang (Horticulturae, 2022)
Magnesium (Mg) is an essential macronutrient in plants and plays a critical role in numerous physiological processes. Therefore, Mg deficiency severely affects plant growth and crop production. This study aimed to investigate the effects of Mg deficiency on plant growth, biomass formation, Mg homeostasis, and photosynthesis of banana seedlings. After exhibiting deficiency symptoms, plants were sprayed with Mg to alleviate the deficiency. Mg deficiency severely reduced plant biomass and chlorophyll content. A significant reduction in maximum quantum yield (Fv/Fm), the effective quantum yield of PS II (ΦPSII), photochemical fluorescence quenching (qP), and non-photochemical fluorescence quenching (NPQ) was observed. In contrast, the light compensation point was almost doubled under Mg deficiency. This indicated damage to the photosynthetic apparatus and photoinhibition under Mg-deficiency treatment. The foliar application of Mg to Mg-deficient plants significantly increased the biomass and reversed the decrease in the biomass of leaves, pseudostem, and corms. More improvement was observed in the leaf area and biomass of the upper leaves. Foliar Mg also increased the Mg concentration in all tissues and enhanced chlorophyll content and chlorophyll fluorescence in leaves. In conclusion, foliar Mg application to Mg-deficient plants efficiently restored banana plant development and might be a practical approach to correcting Mg deficiency in the field.